(3eMV GdESdGe hTQGFY GdOjfs
(3ChdgG (B:s
(3MOKfG YHO GdhGMO eMeO Hf YHOhS GdfjSGHhQi Yf GdaVd Hf TGPGf bGd SCd GdeCehf Cf jcJH eMV GdGSdGe Ydi GdPGcGQ hGdGNJUGQ s
(3BNQgG (B:s
(3hGdUdGI Ydi GdejJ NeS JcHjQGJ aef fbU abO NGda hjQab Hg GPG ONd JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdKGfi YTQs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(12/1035) s
Keywords: (3abg GdePGgH GdCNQis